2017
DOI: 10.1038/nature21366
|View full text |Cite
|
Sign up to set email alerts
|

Amplified stimulated emission in upconversion nanoparticles for super-resolution nanoscopy

Abstract: Lanthanide-doped glasses and crystals are attractive for laser applications because the metastable energy levels of the trivalent lanthanide ions facilitate the establishment of population inversion and amplified stimulated emission at relatively low pump power. At the nanometre scale, lanthanide-doped upconversion nanoparticles (UCNPs) can now be made with precisely controlled phase, dimension and doping level. When excited in the near-infrared, these UCNPs emit stable, bright visible luminescence at a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
513
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 721 publications
(528 citation statements)
references
References 35 publications
8
513
1
6
Order By: Relevance
“…Liu et al. reported that the blue upconversion emission at 455 nm of Tm 3 + ions in UCNPs doped with high concentrations of thulium ions, excited at a wavelength of 980 nm, can be optically inhibited by a laser at 808 nm . Interestingly, in an independent work we observed similar optical inhibition of the 455‐nm emission band of Tm 3 + ions (excited at 975 nm) by the addition of an 810‐nm laser irradiation in high Tm 3 + ‐doped UCNPs .…”
Section: Excitation Manipulation Of Upconversion Nanoparticlessupporting
confidence: 69%
“…Liu et al. reported that the blue upconversion emission at 455 nm of Tm 3 + ions in UCNPs doped with high concentrations of thulium ions, excited at a wavelength of 980 nm, can be optically inhibited by a laser at 808 nm . Interestingly, in an independent work we observed similar optical inhibition of the 455‐nm emission band of Tm 3 + ions (excited at 975 nm) by the addition of an 810‐nm laser irradiation in high Tm 3 + ‐doped UCNPs .…”
Section: Excitation Manipulation Of Upconversion Nanoparticlessupporting
confidence: 69%
“…

and thus abundant PL emissions covering ultraviolet, visible light, as well as infrared region. [13,14] Recently, some reports demonstrated that colloidal CsPbX 3 NCs with Mn 2+ doping exhibited dual-color emission, validating the facile doping in perovskites due to their nonrigid structures. [13,14] Recently, some reports demonstrated that colloidal CsPbX 3 NCs with Mn 2+ doping exhibited dual-color emission, validating the facile doping in perovskites due to their nonrigid structures.

…”
mentioning
confidence: 98%
“…Even after more than several decades of extensive search, rare earth (RE) ions‐doped luminescent nanocrystals (NCs) continue to intrigue research due to its irreplaceable advantages, such as various emission bands and decay lifetime, absence of on‐off blinking and photo‐bleaching, deep excitation penetration, no overlap with cellular autofluorescence, as well as low toxicity, etc . Hence, RE ions‐doped NCs present very broad applications in three‐dimensional display, fluorescence microscopy, nanoscale sensor, security inks, solid state laser, solar cells, and biomedical fields, etc . Among the RE ions‐doped NCs, fluoride compounds with general formula NaReF 4 (Re: Y, Gd, Lu or Sc) because of owning low phonon energy and high chemical stability, have gained more attention .…”
Section: Introductionmentioning
confidence: 99%